2003
DOI: 10.1093/jjco/hyg052
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenesis and Its Modification by Environmental Endocrine Disruptors: In Vivo Experimental and Epidemiological Findings

Abstract: Although a great deal of concern has been raised about the hazard potential of endocrine disruptors present in the environment, the in vivo data available from both experimental and epidemiological studies suggest that the majority of those agents do not pose a risk with regard to cancer development. Indeed, naturally occurring examples such as isoflavonoids even appear to exert protective effects. Only for xenobiotics such as 1,1,1-trichloro-2,2-bis(p-chlorophenyl)ethane (DDT), polychlorinated biphenyls (PCBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 148 publications
0
13
0
Order By: Relevance
“…All the previous mechanisms provide biological plausibility of the studied association; however, their relevance and applicability to carcinogenicity in humans is unknown [16,17]. Moreover, we observed that specific effects on PC cells have been rarely reported.…”
Section: Consistency With Iarc Classification Of Ocpsmentioning
confidence: 69%
See 1 more Smart Citation
“…All the previous mechanisms provide biological plausibility of the studied association; however, their relevance and applicability to carcinogenicity in humans is unknown [16,17]. Moreover, we observed that specific effects on PC cells have been rarely reported.…”
Section: Consistency With Iarc Classification Of Ocpsmentioning
confidence: 69%
“…Interference with endogenous estrogenic or androgenic pathways as agonists or antagonists has been proposed [15]. However, some authors questioned the association between endocrine disrupting compounds and carcinogenesis due to the limited available supporting evidence [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…26 Because phthalates are not covalently bound, they passively leak from the plastic matrix influenced by factors like temperature, exercised pressure, and storage time. [27][28][29][30][31][32][33][34] This leakage is influenced by contact with fluids and by flow rates, and there is documented interaction with body fluids like blood, mucus, and saliva, [14][15][16][17][18][19]22,35 hence, the ban for DEHP plasticized toys that can be chewed on and put in a child's mouth. Remarkably however, and despite this evidence, there is no such ban for the use of DEHP-softened PVC medical devices, which are also put into children's mouths or even beyond.…”
Section: Figure 11mentioning
confidence: 99%
“…28 This overall relationship among blood and biomaterials may explain the sudden occurrence of catheter-related DVT in the 5 patients of the PICU or the sharp increase of CR-DVT incidence in the hospital in 2001. Furthermore, DEHP and its metabolites are known endocrine disruptors modifying carcinogenesis in rats and mice 19,24,36,37 and are genotoxic to human lymphocytes and human mucosal cells. 38 DEHP and its metabolites are also known xenobiotics mimicking or antagonizing sex hormones, hence their established reprotoxicity.…”
Section: Figure 11mentioning
confidence: 99%
See 1 more Smart Citation